Progress on the three Climate-Smart Agriculture pillars towards WBCSD Statement of Ambition - Vermeulen, Sonja J. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2017)
Presented by Sonja Vermeulen, Head of Research, CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), at the World Business Council For Sustainable Development (WBCSD) Climate-Smart Agriculture Strategy Meeting, Montreux, Switzerland on 29 March, 2017.